Alpha-Galactosidase A p.A143T, a non-Fabry disease-causing variant. Issue 1 (December 2016) - Lenders, Malte; Weidemann, Frank; Kurschat, Christine; Canaan-Kühl, Sima; Duning, Thomas; Stypmann, Jörg; Schmitz, Boris; Reiermann, Stefanie; Krämer, Johannes; Blaschke, Daniela; Wanner, Christoph; Brand, Stefan-Martin; et al.
Abstract Background Fabry disease (FD) is an X-linked multisystemic disorder with a heterogeneous phenotype. Especially atypical or late-onset type 2 phenotypes present a therapeutical dilemma. Methods To determine the clinical impact of the alpha-Galactosidase A (GLA) p.A143T/ c.427G > A variation, we retrospectively analyzed 25 p.A143T patients in comparison to 58 FD patients with other missense mutations. Results p.A143T patients suffering from stroke/ transient ischemic attacks had slightly decreased residual GLA activities, and/or increased lyso-Gb3 levels, suspecting FD. However, most male p.A143T patients presented with significant residual GLA activity (~50 % of reference), which was associated with normal lyso-Gb3 levels. Additionally, p.A143T patients showed less severe FD-typical symptoms and absent FD-typical renal and cardiac involvement in comparison to FD patients with other missense mutations. Two tested female p.A143T patients with stroke/TIA did not show skewed X chromosome inactivation. No accumulation of neurologic events in family members of p.A143T patients with stroke/transient ischemic attacks was observed. Conclusions We conclude that GLA p.A143T seems to be most likely a neutral variant or a possible modifier instead of a disease-causing mutation. Therefore, we suggest that p.A143T patients with stroke/transient ischemic attacks of unknown etiology should be further evaluated, since the diagnosis of FD is not probable and subsequent ERT or chaperone treatment should not be an unreflected option.